2017
DOI: 10.1101/232173
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mTORC1 activates PASK-Wdr5 signaling to epigenetically connect the nutrient status with myogenesis

Abstract: SummaryIn the tissue microenvironment, stem cell functions are modulated by extrinsic signaling cues such as peptide hormones and dietary nutrients. These signaling cues maintain the balance between self-renewal and differentiation of its resident stem cells. The mechanistic Target of Rapamycin Complex 1 (mTORC1) is implicated to play an important role in regulating this balance, although its downstream effectors in stem cells have been elusive. We have recently shown that the PASK protein kinase phosphorylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The remaining portion of the human PASK sequence (aa 403-998), approximately 600 amino acids, is considered unstructured but functionally significant. This assertion is based on our recent studies, which identified critical regulatory elements within this unstructured region that regulate PASK subcellular distribution, interactions with the substrate Wdr5, and catalytic activation upon mTORC1-mediated phosphorylation [10][11][12]. Because these biochemical signals primarily target sequences outside the functional domains of PAS-A (PDB-ID: 1LL8) and serine/threonine kinase (PDB-ID: 3DLS), we aimed to understand how these regulatory inputs in the unstructured region of PASK affect the known structural elements that control PASK functions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining portion of the human PASK sequence (aa 403-998), approximately 600 amino acids, is considered unstructured but functionally significant. This assertion is based on our recent studies, which identified critical regulatory elements within this unstructured region that regulate PASK subcellular distribution, interactions with the substrate Wdr5, and catalytic activation upon mTORC1-mediated phosphorylation [10][11][12]. Because these biochemical signals primarily target sequences outside the functional domains of PAS-A (PDB-ID: 1LL8) and serine/threonine kinase (PDB-ID: 3DLS), we aimed to understand how these regulatory inputs in the unstructured region of PASK affect the known structural elements that control PASK functions.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported the catalytic activation of PASK via the mTOR complex 1 (mTORC1)-mediated phosphorylation of residues S640 and T642 within the PAS 1-737 region and S949, T953, and S957 within the C-terminal Kinase 841-1323 region of PASK juxtaposed with the PAC motif (Figure 6F, green circles) [11]. Since these phosphorylation motifs are outside of well-defined domain boundaries, it remains unclear how mTORC1-mediated phosphorylation could stimulate PASK catalytic activity.…”
Section: The Signal-regulatable Quaternary Structure Remodeling Of Pa...mentioning
confidence: 99%
See 2 more Smart Citations